Step
*
of Lemma
implies-isometry-lemma1
No Annotations
∀rv:InnerProductSpace. ∀f:Point(rv) ⟶ Point(rv). ∀r:{r:ℝ| r0 < r} . ∀N:{2...}.
  ((∀x,y:Point(rv).  (x ≡ y 
⇒ f x ≡ f y))
  
⇒ (∀x,y:Point(rv).  ((||x - y|| = r) 
⇒ (||f x - f y|| ≤ r)))
  
⇒ (∀x,y:Point(rv).  ((||x - y|| = (r(N) * r)) 
⇒ ((r(N) * r) ≤ ||f x - f y||)))
  
⇒ {∀x,y:Point(rv).  (((||x - y|| = r) ∨ (||x - y|| = (r(2) * r))) 
⇒ (||f x - f y|| = ||x - y||))})
BY
{ (Auto
   THEN Assert ⌜∀x,y,z:Point(rv).
                  ((y ≡ (r1/r(2))*x + z ∧ (||x - y|| = r) ∧ (||x - z|| = (r(2) * r)))
                  
⇒ ((||f x - f y|| = r) ∧ (||f x - f z|| = (r(2) * r))))⌝⋅
   ) }
1
.....assertion..... 
1. rv : InnerProductSpace
2. f : Point(rv) ⟶ Point(rv)
3. r : {r:ℝ| r0 < r} 
4. N : {2...}
5. ∀x,y:Point(rv).  (x ≡ y 
⇒ f x ≡ f y)
6. ∀x,y:Point(rv).  ((||x - y|| = r) 
⇒ (||f x - f y|| ≤ r))
7. ∀x,y:Point(rv).  ((||x - y|| = (r(N) * r)) 
⇒ ((r(N) * r) ≤ ||f x - f y||))
⊢ ∀x,y,z:Point(rv).
    ((y ≡ (r1/r(2))*x + z ∧ (||x - y|| = r) ∧ (||x - z|| = (r(2) * r)))
    
⇒ ((||f x - f y|| = r) ∧ (||f x - f z|| = (r(2) * r))))
2
1. rv : InnerProductSpace
2. f : Point(rv) ⟶ Point(rv)
3. r : {r:ℝ| r0 < r} 
4. N : {2...}
5. ∀x,y:Point(rv).  (x ≡ y 
⇒ f x ≡ f y)
6. ∀x,y:Point(rv).  ((||x - y|| = r) 
⇒ (||f x - f y|| ≤ r))
7. ∀x,y:Point(rv).  ((||x - y|| = (r(N) * r)) 
⇒ ((r(N) * r) ≤ ||f x - f y||))
8. ∀x,y,z:Point(rv).
     ((y ≡ (r1/r(2))*x + z ∧ (||x - y|| = r) ∧ (||x - z|| = (r(2) * r)))
     
⇒ ((||f x - f y|| = r) ∧ (||f x - f z|| = (r(2) * r))))
⊢ {∀x,y:Point(rv).  (((||x - y|| = r) ∨ (||x - y|| = (r(2) * r))) 
⇒ (||f x - f y|| = ||x - y||))}
Latex:
Latex:
No  Annotations
\mforall{}rv:InnerProductSpace.  \mforall{}f:Point(rv)  {}\mrightarrow{}  Point(rv).  \mforall{}r:\{r:\mBbbR{}|  r0  <  r\}  .  \mforall{}N:\{2...\}.
    ((\mforall{}x,y:Point(rv).    (x  \mequiv{}  y  {}\mRightarrow{}  f  x  \mequiv{}  f  y))
    {}\mRightarrow{}  (\mforall{}x,y:Point(rv).    ((||x  -  y||  =  r)  {}\mRightarrow{}  (||f  x  -  f  y||  \mleq{}  r)))
    {}\mRightarrow{}  (\mforall{}x,y:Point(rv).    ((||x  -  y||  =  (r(N)  *  r))  {}\mRightarrow{}  ((r(N)  *  r)  \mleq{}  ||f  x  -  f  y||)))
    {}\mRightarrow{}  \{\mforall{}x,y:Point(rv).
                (((||x  -  y||  =  r)  \mvee{}  (||x  -  y||  =  (r(2)  *  r)))  {}\mRightarrow{}  (||f  x  -  f  y||  =  ||x  -  y||))\})
By
Latex:
(Auto
  THEN  Assert  \mkleeneopen{}\mforall{}x,y,z:Point(rv).
                                ((y  \mequiv{}  (r1/r(2))*x  +  z  \mwedge{}  (||x  -  y||  =  r)  \mwedge{}  (||x  -  z||  =  (r(2)  *  r)))
                                {}\mRightarrow{}  ((||f  x  -  f  y||  =  r)  \mwedge{}  (||f  x  -  f  z||  =  (r(2)  *  r))))\mkleeneclose{}\mcdot{}
  )
Home
Index